2022
DOI: 10.1056/evidoa2100043
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2/3 Trial of Molnupiravir for Treatment of Covid-19 in Nonhospitalized Adults

Abstract: Molnupiravir is an orally acting novel small-molecule prodrug that acts against Covid-19 by inducing viral mutations to a threshold beyond which it cannot replicate. In a small, double-blind, dose-escalation, trial in non-hospitalized adults with mild/moderate Covid-19 with symptom onset less than 7 days before trial randomization, molnupiravir had with no apparent dose-related effect on adverse events or laboratory tests in relation to dose or treatment. Of the participants receiving molnupiravir 3.1% were ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
130
1
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(136 citation statements)
references
References 19 publications
3
130
1
2
Order By: Relevance
“…Secondary end points, including changes in the WHO Clinical Progression Scale and in patient-reported symptoms of Covid-19, also indicated clinical benefits with molnupiravir over placebo. As in previous trials, 7 , 10 , 23 , 24 , 31 no safety concerns with molnupiravir were identified and there was no evidence of a pattern of clinically meaningful abnormalities in laboratory test results. Since pregnancy was an exclusion criterion in this trial, the potential impact of molnupiravir on fetal development is unknown.…”
Section: Discussionsupporting
confidence: 54%
“…Secondary end points, including changes in the WHO Clinical Progression Scale and in patient-reported symptoms of Covid-19, also indicated clinical benefits with molnupiravir over placebo. As in previous trials, 7 , 10 , 23 , 24 , 31 no safety concerns with molnupiravir were identified and there was no evidence of a pattern of clinically meaningful abnormalities in laboratory test results. Since pregnancy was an exclusion criterion in this trial, the potential impact of molnupiravir on fetal development is unknown.…”
Section: Discussionsupporting
confidence: 54%
“…16 In line with other clinical trials, there were no apparent drug or dose effects on adverse event rates, including no clear impact on mortality. 5,9,10,17,18 As with any new drug, long-term toxicity can only be fully ascertained through ongoing pharmacovigilance.…”
Section: Discussionmentioning
confidence: 99%
“…7 The favorable safety and tolerability profile of molnupiravir seen in preclinical studies and a phase 1 trial provided the needed equipoise for further clinical development. 5,8 The potential of molnupiravir as an antiviral treatment for Covid-19 is being evaluated in two phase 2/3 studies, one in outpatients (MOVe-OUT trial 9,10 ) and the other in hospitalized patients (MOVe-IN trial). In this study, we report safety, efficacy, pharmacokinetic, and virology data from the recently completed phase 2, dose-finding component of MOVe-IN.…”
Section: Introduction Tmentioning
confidence: 99%
“…Molnupiravir is less beneficial when administered late in the disease course — namely, after patients have had symptoms for more than 3 to 5 days or after they are hospitalized, as shown in reports of two phase 2 trials of molnupiravir. 8 , 9 Second, the safety database is small and will require careful monitoring for the emergence of side effects. Third, potential mutagenic toxicity has been a concern, since the drug is mutagenic in Chinese hamster ovary cells.…”
mentioning
confidence: 99%